Study on the Meshing Characteristic of Parallel Axis Line Gear - Chen Yangzhi; Zhu Anshi; Lü Yueling (Jixie chuandong, 2018)
The meshing characteristics of parallel axis line gear including sliding rate,contact ratio,meshing contact model and meshing frequency are studied,comparing to the inherent characteristics of spur gear that covers the node impact,the dynamic transmission error and the meshing impact. The theoretical analysis results show that the parallel axis line gear can fundamentally eliminate the influences of node impact and timevarying stiffness on the vibration and noise of gear transmission. At the same time,the meshing impact frequency of the line gear is low. The simulation results show that the sliding ratio of the parallel axis line gear is equal to zero,and it has the characteristics of steady engagement. A theoretical basis for the vibration and noise research of the parallel axis line gear and its application is provided.